2019
DOI: 10.4992/jjpsy.90.17309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trait self-esteem and self-evaluation threat on the appraisal of close friends

Abstract: People with low self-esteem, when experiencing a threat to self-evaluation, reportedly tend to place higher value in a romantic partner as an indirect form of self-enhancement. This study examined whether such an indirect form of self-enhancement is also found when considering a close friend. Participants' trait self-esteem was measured. Then, they participated in an experiment in which they experienced (or not) a threat to their self-evaluation. They were subsequently asked to evaluate their close friends and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Although ample evidence has shown the moderator roles of self‐esteem in Asia, involving both behavioural and neural data (e.g., Guan et al., 2020; E. S. Kashima et al., 2004; Onoda et al., 2010; Routledge et al., 2010, Study 5; Shimoda & Okubo, 2019; Yanagisawa et al., 2016), cross‐cultural investigations of these roles have been limited. Brockner and Chen (1996) found that high self‐esteem individuals’ self‐bolstering was more robust in the United States than in China when self‐construal was ignored; however, when the latter was taken into consideration, this cultural difference was no longer evident.…”
Section: Core Social Motivesmentioning
confidence: 99%
“…Although ample evidence has shown the moderator roles of self‐esteem in Asia, involving both behavioural and neural data (e.g., Guan et al., 2020; E. S. Kashima et al., 2004; Onoda et al., 2010; Routledge et al., 2010, Study 5; Shimoda & Okubo, 2019; Yanagisawa et al., 2016), cross‐cultural investigations of these roles have been limited. Brockner and Chen (1996) found that high self‐esteem individuals’ self‐bolstering was more robust in the United States than in China when self‐construal was ignored; however, when the latter was taken into consideration, this cultural difference was no longer evident.…”
Section: Core Social Motivesmentioning
confidence: 99%